Activating the Heart : Storytelling, Knowledge Sharing, and Relationship - Szabo-Jones, Lisa, 1969-; Cox, Christopher, 1982-; Christensen, Julia (Writer on homelessness) (Book collections on Project MUSE., 2018)
Explores how storytelling engages and builds new interconnections between people and their histories, environments, and cultural geographies. Focuses on the significance of storytelling in Indigenous knowledge frameworks and other ways of knowing, and how researchers have embraced narrative and story as a part of their methodologies.